Vancomycin-associated acute kidney injury in Hong Kong in 2012–2016 - Qin, Xuzhen; Tsoi, Man-Fung; Zhao, Xinyu; Zhang, Lin; Qi, Zhihong; Cheung, Bernard M. Y. (BMC nephrology, 2020)
To study the incidence of vancomycin-associated acute kidney injury (VA-AKI) in Hong Kong and identify risk factors for VA-AKI. Patients with vancomycin prescription and blood level measurement in 2012-2016 were identified using the Hong Kong Hospital Authority Clinical Data Analysis and Reporting System. Acute kidney injury was defined using KDIGO criteria. Patients without creatinine measurements, steady-state trough vancomycin level or who had vancomycin treatment < 3 days were excluded. Results were analyzed using SPSS version 22.0. Logistic regression was used to identify the predictors for VA-AKI. Odds ratio and 95% confidence interval were estimated. One thousand four hundred fifty patients were identified as VA-AKI from 12,758 records in Hong Kong in 2012-2016. The incidence was respectively 10.6, 10.9, 11.3, 12.2, 11.2% from 2012 to 2016. The incidence of VA-AKI was 16.3, 12.2, 11.3 and 6.2% in patients aged 1-12, 12-60, elderly aged > 60 and newborn and infants, respectively. Baseline creatinine, serum trough vancomycin level, systematic disease history including respiratory failure, hypertension, congestive heart failure, chronic renal failure, anemia and type II diabetes, and concomitant diuretics, piperacillin-tazobactam (PTZ) and meropenem prescription were significantly higher in VA-AKI patients older than 12 years. Logistic regression showed that older age group, higher baseline creatinine, serum trough vancomycin level, respiratory failure, chronic renal failure and congestive heart failure, concomitant diuretics, PTZ and meropenem prescription, and longer hospital stay were all associated with increased risk of VA-AKI. The incidence of VA-AKI in Hong Kong is low but shows no decline. Patients with higher baseline creatinine, multi-organ diseases and multiple drugs administration should have their vancomycin level monitored to decrease the risk of VA-AKI.